Student Organization for Enhancing Competence in Reading Classical Islamic Texts (Kitab Kuning) - Abdul Razak; Ahmad Tanzeh; Binti Maunah (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study investigates how the organization of students contributes to improving competence in reading kitab kuning (classical Islamic texts) in two high-performing Islamic boarding schools, namely Maktuba Bata-Bata and Puncak Darussalam, Pamekasan, Indonesia. While previous studies have primarily examined leadership, curriculum management, and instructional strategies independently, limited attention has been given to organizing students as an integrated managerial process encompassing student organization, delegation of instructional responsibilities, and teacher coordination. Employing a qualitative multiple-case study design, data were collected through participant observation, semi-structured interviews, and document analysis involving kiai, administrators, teachers, students, and parents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by source triangulation and member checking to ensure trustworthiness. The findings reveal that competency-based student grouping, structured learning progression, homogeneous and heterogeneous learning communities, competency-based delegation of teachers' responsibilities, dormitory-based Total Learning Environment, multidimensional teacher mediation, collaborative coordination, ethical communication, and exemplary leadership collectively establish an integrated organizational system that significantly enhances students' competence in reading kitab kuning. The study further proposes the Ethical–Prophetic Managerial Convergence (EPMC) Theory, which explains that sustainable educational quality in Islamic boarding schools emerges through the convergence of formal managerial authority and spiritual authority. The theory extends educational management literature by demonstrating that organizational effectiveness in faith-based educational institutions depends not only on managerial professionalism but also on the integration of ethical leadership, spiritual legitimacy, and collaborative organizational culture. The findings provide both theoretical and practical contributions for strengthening organizational management in Islamic boarding schools while preserving the authenticity of classical Islamic scholarly traditions.